Pengaruh Komunikasi Interpersonal, Profesionalitas Dan Kompetensi Terhadap Sistem Monitoring dan Kinerja Paramedis - Sri Suherning; Toni Herlambang; Eko Budi Satoto (STIE Mandala Jember, 2023)
This study aims to empirically examine the effect of interpersonal communication, professionalism and competence on the monitoring system and paramedic performance. This research was conducted on nurses and midwives who work at the Fatimah Islamic Hospital in Banyuwangi. The research was conducted in April-May 2022. The data collection technique was using a questionnaire. The results showed a positive and significant influence of interpersonal communication on the monitoring system. There is a positive and significant influence of professionalism on the monitoring system. There is a positive and significant influence of competence on the monitoring system. There is a positive and significant influence of interpersonal communication on the performance of nurses. There is a positive but not significant effect of professionalism on the performance of nurses. There is a positive but not significant effect of competence on the performance of nurses. There is a positive and significant effect of the monitoring system on the performance of nurses. There is a positive and significant influence of interpersonal communication on the performance of nurses through the monitoring system. There is a positive and significant effect of professionalism on the performance of nurses through the monitoring system. There is a positive and significant effect of competence on the performance of nurses through the monitoring system.